Perilaku Pejalan Kaki terhadap Pemanfaatan Jalur Pedestrian di Kawasan Perdagangan - Fendy Faizal Gobel (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2016)
This research aimed to analyze the pedestrian behavior toward the utilization of pedestrian ways at the commerce area at Soeprapto street corridor, Gorontalo city. This research was conducted directly at the place and time where the research being observed. There were two kinds of the behavioral mapping used in this research; those were Place Centered Mapping and Person Centered mapping. The result of this research was showing that the area of pedestrians at Soeprapto street, Gorontalo city it has already been not appropriate with the theory considering within its function and contentment. It was because it was also used for other various activities rather than walking. Pedestrian trackswere actually open area that ought to be used for walking rather than other activities, so that it will not change the behavioral pattern in utilizing the tracks